The Paradox of Technological Progress and the Ethical Crisis in Digital Civilization - Nopit Ernasari; Naib; Adithya Tri Firmansyah (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
The advancement of digital technology has significantly transformed various aspects of human life while creating new opportunities for increasingly sophisticated cybercrime. This phenomenon reflects an ethical crisis in digital civilization, characterized by declining moral responsibility in the use of digital technology. Although cybercrime has been widely examined from technological and criminal law perspectives, limited attention has been given to integrating digital ethics, digital literacy, and legal responses into a comprehensive preventive framework. This study aims to analyze the relationship between digital technological advancement and the emergence of cybercrime as a manifestation of this ethical crisis, as well as to examine preventive strategies through law enforcement, digital ethics, and digital literacy. This research employs normative legal research with a descriptive qualitative approach. Data were collected through library research, including legislation, books, scholarly journals, and official documents, and were analyzed using qualitative content analysis. The findings reveal that digital technology has improved efficiency and access to information while facilitating hacking, data theft, online fraud, malware distribution, and privacy violations. These developments demonstrate that technological progress without ethical awareness may undermine trust and security in the digital environment. The study’s novelty lies in proposing an integrated legal framework that combines adaptive law enforcement, digital ethics, and digital literacy as complementary strategies for cybercrime prevention. Its main legal contribution is the development of a normative approach that strengthens preventive legal policies beyond conventional punitive measures. The findings also provide practical guidance for policymakers, law enforcement agencies, educational institutions, and digital stakeholders in fostering a secure, ethical, and sustainable digital ecosystem.